Construction of a Conceptual Model of the Accounting and Analytical System of Report Formation Under IFRS - Бруханський, Руслан Феоктистович; Spivak, Serhii; Korolyuk, Tetyana; Krepych, Svitlana; Nita, Bartłomiej (IEEE, 2023)
As a result of the study, the mechanism of modeling the accounting process at the present stage is considered and a conceptual model of formation of accounting and management reporting in the context of transition to IFRS is built. The necessity of developing a mechanism for the formation of management accounting policy aimed at preparing information in accordance with IFRS requirements, which increases the degree of reliability of information and allows optimizing the process of making management decisions at various levels of management, is proved. The article analyzes the methods of obtaining IFRS reporting by Ukrainian enterprises and develops a model of automated processing of accounting information using the combined method of reporting. The proposed methodology will automate the preparation of financial and management reports of enterprises in the context of transition to international accounting standards. The practical significance of the obtained results lies in the possibility of using the developed scientific and methodological recommendations, models and methods, which, in accordance with the principles of international financial reporting standards, will help to improve the quality of information resources and increase the efficiency of economic resources of business entities
Keywords: IFRS; modeling; conceptual model; accounting policy (AP); financial reporting; transformation of financial reporting; management reporting